Development of lateral flow enzyme substrate assay strip for qualitative estimation of coliforms - Gawai, Kunal Manohar; Hati, Subrota; Prajapati, Jashbhai (Indian Journal of Dairy Science, 2024)
FSSA 2011 has adopted a conventional IS-5887 (Part-I) 1976 and IS-5401 Part-1 (2012) protocol for monitoring of E. coli and coliforms in dairy products respectively. These methods are time consuming and sometimes requires further isolation and confirmation to finalize the true contaminant. The current investigation was carried out to minimize these limitations in detection of coliforms and Escherichia coli and to give a real time test to the industry that meets legal limits on day to day basis.The present investigation comprised of development of protocol for qualitative detection of coliforms in spiked samples using sonication technique and enzyme substrate assay. A protocol developed for sample preparation by extracting β-galactosidase (β-gal) using ultra sonicator (amplitude 80% and time 15 minutes) to give a positive ONPG test results within 20 minutes. After finalizing the sample preparation protocol, specific amount of the extract was used to check the presence of coliforms by using X-gal impregnated absorbent strip. Sensitivity of X-gal test was very good as it could detected minimum 10 cells/10 ml of spiked coliforms sample. It turned white strip in to blue colour indicating qualitative presence of coliforms within 20 minutes at 37 oC.